The Effect of Information Technology Investment Governance on Information Technology Performance and Organizational Performance: a Case Study - Izza Ashsifa; Syaiful Ali (The Indonesian Journal of Accounting Research, 2019)
The increase in information technology (IT) investment and organizational competition are the reasons for the evaluation of investment decisions in the IT field. The evaluation that needs to be done is to set priorities for IT investments, given the limited resources and human resources. The determination of IT investment priorities must be carefully considered by managing effective IT investments to provide positive results for the organization. The purpose of this research is to investigate IT investment governance and to investigate how to determine and govern IT investment projects' priorities in improving IT performance and organizational performance at one of the largest universities in Indonesia. The method used in this research is a qualitative method. Data collection techniques in this study are interviews and document reviews, and the NVIVO application is used to analyze the data. The results of the study show that IT investment governance at the university is still in the process of development, but has been implemented quite good. This is indicated by the existence of functional structures, processes, and relational mechanisms that are following several policies and regulations applied at the university. Although it has been carried out quite well, IT investment governance cannot be said to be effective because it still has weaknesses, namely that the university still does not have a clear IT governance standard or framework.